(untitled) (Research, Society and Development, 2022)
Burnout syndrome is characterized as an aggravation of stress, of a persistent character, related to occupation relationships, and there are three dimensions: exhaustion, professional achievement and depersonalization. Some indicators suggest that the stress generated in students in the health area, due to the rigorous study routine, would place them as victims of this syndrome. This study aimed to verify the manifestation of Burnout syndrome in students of the basic cycle of the undergraduate medical course at UFMA-Pinheiro. Validated questionnaires were applied to assess the syndrome in this group, aiming to assess the students’ stress level. As for the statistical analysis, initially all variables were analyzed descriptively. For quantitative variables, this analysis was performed by observing the minimum and maximum values, and calculating means and standard deviations. For qualitative variables, absolute and relative frequencies were calculated. The study was developed with 98 people, where high emotional exhaustion was present in 46.94% of the students, cynicism and depersonalization was found in 30.61% of the academics and 46.94% of the students had a low level of effectiveness. The profile most affected by Burnout syndrome was female students with low income and fewer hours of leisure. Prevention can be performed in the group in question and, when the prevalent factors of the syndrome in this group are known, this measure will enable the formation of more empathetic doctors dedicated to caring for the community.